2021
DOI: 10.1111/jcmm.16729
|View full text |Cite
|
Sign up to set email alerts
|

Primary ciliogenesis is a crucial step for multiciliated cell determinism in the respiratory epithelium

Abstract: The alteration of the mucociliary clearance is a major hallmark of respiratory diseases related to structural and functional cilia abnormalities such as chronic obstructive pulmonary diseases (COPD), asthma and cystic fibrosis. Primary cilia and motile cilia are the two principal organelles involved in the control of cell fate in the airways. We tested the effect of primary cilia removal in the establishment of a fully differentiated respiratory epithelium. Epithelial barrier integrity was not altered while mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…Primary ciliogenesis is a necessary step during the cell cycle to orchestrate the fate of the two daughter cells: non-differentiated cells (able to form a PC) and differentiated cells (either MCC or secretory cells). Primary cilia are transient in homeostasis but their dysregulation (loss or maintenance) may induce an alteration of cell fate as we recently evidenced during AEC differentiation [ 27 ]. In COPD, the increase of PCC suggested that non-differentiated cells did not progress through the cell cycle and were blocked in G0.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Primary ciliogenesis is a necessary step during the cell cycle to orchestrate the fate of the two daughter cells: non-differentiated cells (able to form a PC) and differentiated cells (either MCC or secretory cells). Primary cilia are transient in homeostasis but their dysregulation (loss or maintenance) may induce an alteration of cell fate as we recently evidenced during AEC differentiation [ 27 ]. In COPD, the increase of PCC suggested that non-differentiated cells did not progress through the cell cycle and were blocked in G0.…”
Section: Discussionmentioning
confidence: 99%
“…Micrographs were acquired on a Zeiss AxioImager microscope (20× Ph and 63×) with ZEN software (version 8.1, 2012, Zeiss, Marly le Roi, France) and processed with ImageJ (National Institutes of Health, version 2.2.0, Bethesda, MD, USA) for analysis. We routinely control the specificity of the cilia labelling with co-staining and we perform negative and positive controls for each set of experiment [ 11 , 27 ]. The density of multiciliated cells (MCC) was evaluated with the average pixel density of the fluorescence associated to cilia staining as previously described [ 10 ].…”
Section: Methodsmentioning
confidence: 99%
“…A correlation between the decreased number of PCC and that of MCC in COPD small airway epithelium could be expected. Indeed, it was previously reported that PC removal of airway undifferentiated cells led to impairment of multiciliogenesis [10] and that murine tracheal MCC originated from PCC [13]. However, in COPD bronchial epithelium, the number of PCC is markedly increased, especially in areas of epithelium remodelling, suggesting the involvement of PC in altered epithelial repair/regeneration processes in COPD [4].…”
Section: Grhl2mentioning
confidence: 99%
“…(forward-5'-CTTTACCTGGGACGTGAATGA-3', reverse-5'-GGAAGTCCTTTCACCCCTTT-3'), RFX3 (forward-5'-ACCTCAACCGTGTCGACTTT-3', reverse-5'-GCTGCTGAAGCATCTTGAAGT-3'), SCGB1A1, FOXJ1, MUC-5AC, HEATR2, MCIDAS and RFX2, all previously described [3,10]. Results were normalized to the housekeeping gene GAPDH expression [3,10]. Relative expression (ΔΔCt) was expressed as fold change from ALI D0 values of each gene in each group.…”
Section: Grhl2mentioning
confidence: 99%
See 1 more Smart Citation